Evidence-Based Strategies for Optimizing Management of Cystic Lesions in Elongated Tubular Skeletal Structures (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Cystic lesions of long tubular bones remain one of the most challenging orthopedic pathologies in pediatric and adolescent patients due to their tendency toward progression, repeated pathological fractures, deformation of the affected segment, and high recurrence rates following conventional treatment. The need for a treatment strategy that ensures radical removal of the cystic cavity, full restoration of bone architecture, prevention of relapse, and preservation of limb function has stimulated the development of advanced minimally invasive and reconstructive approaches. The present method is based on combining radical surgical excochleation of the cystic focus with reconstruction of the bone defect using various interchangeable osteoplastic materials, including autologous bone grafts, medical cement, collopan preparations, and modern bone-substitute grafts. This multimodal technique enables stable filling of the defect, stimulates osteogenesis, and provides conditions for reliable structural repair.A key component of the method is the use of transosseous osteosynthesis based on Ilizarov technology, which makes it possible to perform controlled reposition, compression, distraction, and correction of deformities while preserving vascular supply and biological integrity of the bone. Endoscopic visualization is applied as an auxiliary technique to monitor the radicality of the resection, minimize surgical trauma, and reduce the risk of recurrence. The effectiveness of the method was evaluated in children and adolescents with cystic lesions of the proximal femur, complicated in many cases by deformities, repeated fractures, or limb-length discrepancies. The combination of directed osteotomy, osteoplastic reconstruction, and controlled external fixation provided reliable conditions for the formation of high-quality bone regenerate, early functional recovery of the limb, and restoration of physiological biomechanics.Long-term radiological and functional outcomes confirm that the described method offers significant advantages over traditional techniques. It ensures complete remodeling of the bone without recurrence, preserves joint mobility, corrects deformities, restores limb length, and reduces the total duration of treatment by 1.5–2 times.